PERAN FOOTBALL AGAINST RACISM IN EUROPE DALAM MENGATASI RASISME DALAM SEPAKBOLA DI LIGA ITALIA PERIODE 2013-2019 - Adithya Yogatama (2020)
This research discusses how efforts to overcome racism in the Italian League by Federazione Italiana Giuoco Calcio (FIGC) in implementing the Football Against Racism in Europe (FARE) program for the 2013-2019 period. The geographical location adjacent to the African continent makes the migration of African citizens to Italy. During Benito Mussolini's reign, oppression of migrants was permitted so that African citizens who migrated to Italy felt oppressed. The African citizen had no place in the Italian region and could not do any work. Since that time racism against people of black race has been very rampant both physical actions such as murder or beatings and verbally such as insults against those committed by native Italian citizens. In the field of football, racism in the Italian League is a very big problem because it has happened since the 1990s which was accepted by Paul Ince, a black English footballer who moved to the Italian league. Since then racism in the field of football has increased every year. Actions such as racist songs, screams mimicking the sounds of monkeys, and banners that contain messages like Italy do not need black people very often in every game. This urgency is the background for the formation of FARE. This step was taken in an effort to release the level of racism in the Italian Region.